TRADITIONALLY USED MEDICINAL PLANTS FOR WOUND HEALING IN THIRUVALLUR DISTRICT, TAMIL NADU, INDIA - I. D., KASINATHAN; S., UMA; K., ELUMALAI; MANIVANNAN, KAVITHA; RAMASAMY, MALATHI (International Journal of Current Pharmaceutical Research, 2024)
The present study aims to enumerate the ethno-medicinal uses of plants by the Irular communities residing around the Thiruvallur district. The medicinal use of (49) plants belonging to 39 families was identified and recorded by the tribes, along with their botanical identities and methods of drug preparation. The drugs administered locally to heal wounds, including antibiotics, antiseptics, etc., and the necessary information related to the traditional medicinal plants were highlighted in this paper. Wound healing activity is a cellular and biochemical process for restoring the original structure and functions of damaged tissue. The wound may occur from a physical, chemical, thermal, microbial, or immunological insult to the tissues. Various parts of the plants have been in use for several years in tribal communities, traditionally for treating many diseases like skin, colic, sores, cancer, etc. Due to their minimal side effects. The natural agents present in the plants induce wound healing and regeneration from tissue loss by multiple mechanisms. Plant extracts have immense potential for the treatment of wound healing activity. In this review, we focused on the wound healing activity with the pharmacological process of medicinal plants.